Effect of serum from Vitamin E-supplemented calves on Infectious Bovine Rhinotracheitis Virus replication - P.G. Reddy; J.L. Morrill; H.C. Minocha; R.A. Frey (Kansas Agricultural Experiment Station Research Reports, 1985)
Blood serum from Holstein calves supplemented with vitamin E at levels of 2800 mg orally or 1400 mg by injection at weekly intervals inhibited replication of Infectious Bovine Rhinotracheitis Virus in tissue cultures. Supplementing typical calf diets with vitamin E may increase protection against pathogens, at a time when they are more vulnerable to problems such as respiratory diseases.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Serum; Vitamin E; Infectious Bovine Rhinotracheitis Virus; Respiratory disease